2017
DOI: 10.51723/ccs.v27i01.88
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de Estudos da Rede Brasileira de Avaliação de Tecnologia em Saúde (Rebrats) de 2004 a 2015

Abstract: Introdução: A Rede Brasileira de Avaliação de Tecnologia em Saúde (Rebrats) atua na produção e disseminação de estudos para analisar eficácia, segurança, efetividade e custo‑efetividade de tecnologias em saúde. Objetivo: Traçar o perfil dos estudos concluídos pelos membros da rede no período de 2004 a 2015. Método: Realizou‑se estudo descritivo, com base no banco de dados do sistema de informação da REBRATS. As seguintes variáveis foram investigadas: ano e tipo de estudos, agravos para os quais as tecnologias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The result of this study showed that some characteristics of the reports (type of technology and the requester’s profile) predict the incorporation, and are not directly related to the criteria settled down. Previous studies that characterized the CONITEC by other methods, in particular descriptive analysis, showed a similar profile, with the drug technology being the most evaluated and approved, and the “government” claimant having the highest number of approved technologies (4;9;39).…”
Section: Discussion and Implementation Considerationmentioning
confidence: 63%
See 1 more Smart Citation
“…The result of this study showed that some characteristics of the reports (type of technology and the requester’s profile) predict the incorporation, and are not directly related to the criteria settled down. Previous studies that characterized the CONITEC by other methods, in particular descriptive analysis, showed a similar profile, with the drug technology being the most evaluated and approved, and the “government” claimant having the highest number of approved technologies (4;9;39).…”
Section: Discussion and Implementation Considerationmentioning
confidence: 63%
“…Over the years, several HTA agencies have been created in different countries with the purpose of improving decision-making regarding investments and disinvestments in health. These HTA processes have been the object of several studies to compare differences and similarities between them (e.g., criteria, health priorities, challenges or limitations, among other aspects) (2)(3)(4). Heupink et al (5) highlight that the HTA process requires time and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 15 studies offered a comprehensive assessment of HTA in Brazil. Specifically, two studies were based on surveys with Brazilian experts about the HTA implementation in Brazil [19,31], five studies were opinion pieces presenting a critical appraisal on the current HTA institutions in Brazil [8,10,24,25,36], seven were reviews of the Brazilian HTA reports [15,16,18,20,26,27,38], and one study was a literature review addressing the use of real-world data on Latin America [22].…”
Section: Development Of the Questionnairementioning
confidence: 99%